2017
DOI: 10.1017/rdc.2017.49
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Ecology of the Land Snail Helix Melanostoma in Northeastern Libya

Abstract: Terrestrial gastropods are problematical for radiocarbon because they tend to incorporate carbon from ancient sources as a result of their dietary behaviour. The radiocarbon ecology of the pulmonate land snail, Helix melanostoma in Cyrenaica, north eastern Libya, was investigated as part of a wider study on the potential of using terrestrial mollusc shell for radiocarbon dating of archaeological deposits. H. melanostoma was selected out of the species available in the region as it has the most predictable radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Accordingly, the results support our hypothesis of real multimillennial age mixing of shells within colluvial deposits from The Desertas Islands. The scale of age mixing documented here was not significantly impacted by potential dead carbon intake by the snails (e.g., Hill et al, 2017), because the studied islands are poor in carbonate sediments and recently dead (modern) shells yielded 14 C ages younger than ~300 years that could potentially be explained by a post-bomb effect after the 1950s (Quarta et al, 2007). Even if snails’ carbonate intake is possible, the effects of carbonate ingestion (<300 years) cannot explain the large degree of age mixing within colluvial sediments (>6 ka).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Accordingly, the results support our hypothesis of real multimillennial age mixing of shells within colluvial deposits from The Desertas Islands. The scale of age mixing documented here was not significantly impacted by potential dead carbon intake by the snails (e.g., Hill et al, 2017), because the studied islands are poor in carbonate sediments and recently dead (modern) shells yielded 14 C ages younger than ~300 years that could potentially be explained by a post-bomb effect after the 1950s (Quarta et al, 2007). Even if snails’ carbonate intake is possible, the effects of carbonate ingestion (<300 years) cannot explain the large degree of age mixing within colluvial sediments (>6 ka).…”
Section: Discussionmentioning
confidence: 71%
“…Only small patches of colluvial silty-clay sediments with minor content of biogenic eolian carbonates (Goodfriend et al, 1996) can be found scattered around these two islands. Due to the lack of extensive carbonate-rich sediments and limestone throughout the Desertas Islands, the potential incorporation of dead carbon into snail shells (Pigati et al, 2004, 2010; Quarta et al, 2007; Hill et al, 2017) is likely limited in the study area.…”
Section: Study Area Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(*) Terrestrial snails may incorporate carbon from ancient sources as a result of their dietary behaviour thus providing older radiocarbon ages (Hill et al, 2017).…”
Section: Notesmentioning
confidence: 99%
“…Biogenic carbonates also offer the additional advantage that they can be directly dated using methods such as radiocarbon (e.g. Magnani et al 2007;Butler et al 2009a;Reimer 2015;Bosch et al 2015b;Hill et al 2017), U-Th series (e.g. Magnani et al 2007;Rowe et al 2015), or amino acid racemisation (e.g.…”
Section: Seasonal Records and Human Activitymentioning
confidence: 99%